2021
DOI: 10.1186/s10020-021-00387-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of ERBB4 mutations in the prognosis of advanced non-small cell lung cancer treated with immune checkpoint inhibitors

Abstract: Background Immune checkpoint inhibitors (ICIs) have witnessed the achievements of convincing clinical benefits that feature the significantly prolonged overall survival (OS) of patients suffering from advanced non-small cell lung cancer (NSCLC), according to reports recently. Sensitivity to immunotherapy is related to several biomarkers, such as PD-L1 expression, TMB level, MSI-H and MMR. However, a further investigation into the novel biomarkers of the prognosis on ICIs treatment is required. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In another study, Wang et al showed that overexpression of miR-551b, a regulator of the gene ERBB4 , may predict poor prognosis in patients with PTC ( 36 ). For instance, ERBB4 could be downregulated in thyroid tumors; hence, this miRNA could be considered a novel biomarker ( 49 ).…”
Section: Analysis Of Micrornas In Tumoral Tissue Of Ptcmentioning
confidence: 99%
“…In another study, Wang et al showed that overexpression of miR-551b, a regulator of the gene ERBB4 , may predict poor prognosis in patients with PTC ( 36 ). For instance, ERBB4 could be downregulated in thyroid tumors; hence, this miRNA could be considered a novel biomarker ( 49 ).…”
Section: Analysis Of Micrornas In Tumoral Tissue Of Ptcmentioning
confidence: 99%
“…The majority of gene alterations implicated in our model, including PTPRT , EPHA3 , ERBB4 , ATRX , PTPRD , AMER1 , TERT , HGF , POLE , NTRK3 , EPHA5 , ALK , and PGR , were positively correlated with the high-score group and favorable ICI responses. For some of these genes, like PTPRT [ 37 , 38 ], PTPRD [ 38 ], ERBB4 [ 39 ], ATRX [ 40 ], TERT [ 41 ], POLE [ 8 ], NTRK3 [ 42 ], EPHA5 [ 43 ], and ALK [ 14 ], previous literature has highlighted their potential roles as biomarkers for ICIs therapy in NSCLC. Our study firstly reported the significance of EPHA3 , AMER1 , HGF , and PGR alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al found that ARID1A mutation could serve as predictive biomarkers for the prognosis of ICIs [ 28 ]. Besides that, some studies show ERBB4 mutation and FGFR4 mutation could serve as a potential biomarker for the prognosis of NSCLC with ICIs treatment [ 29 , 30 ]. With the increasing routine of NGS in clinical practice, it is essential to explore predictors factors of response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%